2017
DOI: 10.4038/cmj.v62i3.8515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5 IU oxytocin bolus and 20 IU oxytocin infusion compared to 5 IU oxytocin bolus and normal saline infusion in the control of blood loss during and after ante-partum lower segment caesarean section: a randomized controlled trial

Abstract: Introduction Obstetric haemorrhage is the leading cause of maternal mortality worldwide and in most cases it relates to uterine atony. Even though an oxytocin bolus is used routinely, additional infusion of oxytocin may be required if haemorrhage occurs.Objectives To compare the effects of 20 IU oxytocin infusion and 5 IU bolus with 5 IU bolus and 500ml normal saline on the control of blood loss in antepartum lower segment caesarean section.Methods A double-blind randomized controlled trial was conducted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…There were no statistically significant differences between groups (P=0.67). In agreement with our study, the study of Kajendran et al (14) reported that there was no significant difference in mean length of stay in theatre and recovery in the intervention group (116.6 ± 56.0 minutes) and the control group 112.6 ± 46.8 minutes (p= 0.08).…”
Section: Discussionsupporting
confidence: 93%
“…There were no statistically significant differences between groups (P=0.67). In agreement with our study, the study of Kajendran et al (14) reported that there was no significant difference in mean length of stay in theatre and recovery in the intervention group (116.6 ± 56.0 minutes) and the control group 112.6 ± 46.8 minutes (p= 0.08).…”
Section: Discussionsupporting
confidence: 93%
“…Duffield compared low and high doses of oxytocin given as a continuous infusion. That study confirmed the previously mentioned result that both low (10 IU) and high (60 IU) infusion of oxytocin works in the same preventive regime [18].…”
Section: Discussionsupporting
confidence: 91%
“…The blood loss in the group of 20 IU oxytocin infusion was significantly less ( p = 0.046). Visual estimation of blood loss made by the surgeon ( p = 0.01) and anesthetist ( p = 0.03) was also significantly higher in the placebo group [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the review of the medical records, we found that the trigger "intravenous injection of calcium gluconate" was triggered 15 times (principally in patients with eclampsia or pre-eclampsia), but that no ADE was noted. Studies have shown that Ca + 2 stimulated neuromuscular excitement and promoted blood coagulation, and the intravenous injection of calcium gluconate before cesarean section reduced the amount of oxytocin, intraoperative and postoperative bleeding, and effectively prevented postpartum hemorrhage [53,54]. The condition of this trigger entry should therefore be de ned as "intravenous injection of calcium gluconate and Mg > 5 mmol•L − 1 .…”
Section: Revision Of Triggers Re Ecting a Low Ppvmentioning
confidence: 99%